From fresh water to the slope: fish community ecology in the Río de la Plata and the sea beyond - García, Mirta L. (2010)
The spatial pattern of fish assemblages and its relationship with factors along an environment gradient, from fresh to marine water environment along the Río de la Plata estuary (36ºS, 56ºW) the shelf and part of the slope, was examined using data from 22 sampling stations. Fish were sampled from all station with an Engel type trawl (200 mm stretched mesh in the wings, 120 mm stretched mesh in the cod ends, 4 m vertical opening and 15 m horizontal aperture) towed at 4 knots for 20 to 30 min per set. Cluster analysis and ordination analysis MDS were used to define spatial distribution of fish assemblages based on fish composition (abundance and biomass). BIO-ENV process was used to estimate assemblage association with depth, temperature and salinity of surface and bottom waters. The results of these analyses showed that the fish community along the riverine-marine gradient was structured in four assemblages: riverine, estuarine, shelf and slope. These assemblages were found to differ significantly in their species composition. Each assemblage was characterized by several common and discriminator species and characterized by differing environmental conditions. Bottom salinity and bottom temperature were the environmental variables most strongly associated with differences in assemblage structure across the various areas. The changes in assemblage structure between areas were gradual, with no sharp boundaries.